Introduction of industrial psychology I - Mohd Ghani, Awang (Penerbit UMP, 2017)
Psychology is a scientific study of all forms of human behaviour and the science of mind or mental state and process characteristics of a person. Behaviour and thinking paradigm are two main factors which affect human habits and attitudes conditioning in their self-concept and personality. This behaviour may influence all aspect of activities in everyday life, working atmosphere, community activities, leisure, religious and etc.